Distribution of Rotundone and Possible Translocation of Related Compounds Amongst Grapevine Tissues in Vitis vinifera L. cv. Shiraz - Zhang, Pangzhen; Fuentes, Sigfredo; Wang, Yueying; Deng, Rui; Krstic, Mark; Herderich, Markus; Barlow, Edward W. R.; Howell, Kate (Frontiers in Plant Science, 2016)
Rotundone is an attractive wine aroma compound, especially important for cool climate Shiraz. Its presence in wine is mainly from the grape skin, but can also be found in non-grape tissues, such as leaves and stems. Whether rotundone is produced independently within different grapevine tissues or transported amongst non-grape tissues and grape berries remains unclear. The current study investigated the distribution of this compound in different vine tissues during development and studied the most likely mode of rotundone translocation - via phloem – using stable isotope feeding. In addition, local production of rotundone induced by herbivore feeding was assessed. Results showed that rotundone was firstly detected in the petioles and peduncles/rachises within the development of Vitis vinifera L. cv. Shiraz. Different grapevine tissues had a similar pattern of rotundone production at different grape developmental stages. In the individual vine shoots, non-grape tissues contained higher concentrations and amounts of rotundone compared to berries, which showed that non-grape tissues were the larger pool of rotundone within the plant. This study confirmed the local production of rotundone in individual tissues and ruled out the possibility of phloem translocation of rotundone between different tissues. In addition, other terpenes, including 1 monoterpenoid (geraniol) and six sesquiterpenes (clovene, α-ylangene, β-copaene, α-muurolene, δ-cadinene, and cis/trans-calamenene) were, for the first time, detected in the EDTA-facilitated petiole phloem exudates, with their originality unconfirmed. Unlike other herbivore-induced terpenes, herbivorous activity had limited influences on the concentration of rotundone in grapevine leaves.